Student engagement and adjustment to college among undergraduate students - Goudih, Zohra; Abdullah, Ssekamanya Siraje; Benraghda, Abdelmadjid (University of Idaho Library, 2018)
Student engagement and adjustment to college are important factors that contribute to their success. This study aims to investigate the relationship between these two variables and the differences that can be drawn in the context of undergraduate students at International Islamic University of Malaysia (IIUM). Three types of adjustments namely; (academic adjustment, social adjustment, and personalemotional adjustment) were measured by SACQ. In addition, three types of student engagements (peer-to-peer engagement, engagement with faculty, and engagement with the university) were assessed using the accredited National Survey of Student Engagement (NSSE). 446 students were involved in the current study. ANOVA, t-test, and correlation analysis were used. The findings of this study revealed a moderate relationship between adjustment to college and student engagement r =487. The overall findings suggest relatively low involvement which would allow the institution the opportunity to develop their programs to increase student engagement and encourage students to graduate on time.